Application of microbial polymer hydrogel for development of bioreceptor based biosensor. - Singh, Narinder (My University, 2018)
Pesticide residues present in food crops continue to pose a serious concern to human health. Though rapid detection methods for these are crucial for timely intervention, of the several that has been developed, economical and simple methods are presently much sought after. Biomaterials such as biopolymers have recently been investigated as reliable options for biosensors and may provide economical and sustainable options. In an effort to develop a biopolymer-based biosensor for organophosphorus pesticides, microbial polymers were screened with amphiphilic properties and one with good amphiphilicity was selected for analyzing its hydrogelling function. The polymer characteristics were further determined by Scanning electron micrograph (SEM), Fourier transform infrared spectroscopy (FTIR) and Xray diffraction (XRD). The selected polymer was used for synthesizing the hydrogel and compared visually with poly-vinyl alcohol (PVA) and PVA-Chitosan hydrogels, for their efficacy (Swelling kinetics). The microbial polymer possessed excellent characteristics and swelling property in comparison to the others. The activity, inhibition kinetics were optimized for acetylcholinesterase (AChE) enzyme with indoxyl acetate as substrate and dichlorvos (organophosphorus pesticide) as its inhibitor. For fabrication of the biosensor, acetylcholinesterase (as bioreceptor) was encapsulated in microbial polymer hydrogel. The AChE based biosensor was then evaluated by analysing dichlorvos residues from commonly consumed food items: cabbage, cauliflower, rice, brinjal, milk and water spiked with various concentrations of pesticide. The results indicated a visual colour change representing response with increasing concentrations. A concentration of dichlorvos ranging above 5 ppm to 100 ppm could be interpreted based documented semiquantitatively using ImageJ software for image analysis.The results of this study imply further possibility of refining this method for developing a cost effective and simple kit.
Keywords: Microbial polymer; Hydrogel; Acetylcholinesterase (AChE); Indoxyl acetate; Dichlorvos; Organophosphorus; Biosensor